ANALISIS PENGEMBANGAN SARANA DAN PRASARANA PASAR TRADISIONAL OLEH DINAS PASAR KOTA PEKANBARU: (STUDI KASUS PASAR CIK PUAN) - Ardian Pradinata; Arief Rifa'i H (UIR Press, 2018)
This research at indication to know objektiflevel of development infrastructures of Cik Puan traditional market by market office Pekanbaru. Development assessment indicators used planning, execution, movement and observation. This study located in Market office Pekanbaru and Cik Puan Market. There are two groups of population and sample, 17 employees of the development of facilities and infrastructure department on the Market office and 41 traders from Cik Puan Traditional Market Pekanbaru. This study using three sampling techniques, Purposive technique used to determine individual sample, Saturated sampling technique or Census used for population group of development of facilities and infrastructure department employees and Incidental sampling technique used for population group of Cik Puan Traditional Market Pekanbaru traders. Types and data collection techniques consist of primary and secondary data. Data analyzing technique used is by using descriptive method to analyzing the available data on the studied object and comparing with theory-related problems. Furthermore, both quantitatively and qualitatively analyzed further to comparing the reality and references from this studied, and then described briefly and clearly. Based on analysis technique, researcher conclude that Development Analysis of Traditional Market Infrasturctures By Market Office Pekanbaru ( Cik Puan Market Case Study ) is in the interval assessment has not been good enough. Recommendations that should be considered, mainly for the development of infrastructure to make a more appropriate plan, timely implementation of activities, a good socialization, and an effective observing and monitoring to make comfortable place for buying and selling process.